Playing with pop-ups : the art of dimensional, moving paper designs - Hiebert, Helen, 1965- (Beverly, MA : Quarry Books, 2014)
"Enter the enchanting world of pop-ups and handmade paper crafts. Join author Helen Hiebert as she guides you through the materials, tools, and basics of pop-up structures and movable mechanisms, including parallel folds, angle folds, and volvelles--just to name a few. Enjoy creating projects such as pop-up earrings, an accordion, a skyline, a carousel house, a tunnel book, a puppy puppet, and more! ... The book also features a stunning gallery of work by acclaimed pop-up artists whose beautiful work will inspire you to expand on your own amazing movable paper creations"--Back cover blurb.
Getting started : cut, score, fold, pop! --Projects to play with : artistic ideas for popping, engineering, and moving paper --Gallery : discovering new realms by turning the page.
Offset printed sewn signatures, sewn into a soft paper cover.
Includes bibliographical references (page 143).
Keywords: Pop-up books -- Handbooks, manuals, etc; Artists' books -- Handbooks, manuals, etc; Paper work; Cut-out craft